Uncompensated magnetization and exchange-bias field in La 0.7Sr0.3MnO3/YMnO3 bilayers: The influence of the ferromagnetic layer - Zandalazini, Carlos Ivan (2011)
We studied the magnetic behavior of bilayers of multiferroic and nominally antiferromagnetic o-YMnO3 (375 nm thick) and ferromagnetic La 0.7Sr0.3MnO3 and La0.67Ca 0.33MnO3 (8...225 nm), in particular the vertical magnetization shift ME and exchange-bias field HE for different thickness and magnetic dilutions of the ferromagnetic layer at different temperatures and cooling fields. We have found very large M E shifts equivalent to up to 100% of the saturation value of the o-YMO layer alone. The overall behavior, including XMCD magnetization shift measured at the Mn-L edge of the LSMO layer only, indicates that the properties of the ferromagnetic layer contribute substantially to the ME shift and that this does not correlate straightforwardly with the measured exchange-bias field HE.